Estudio del patrimonio inmaterial del ámbito 1: tradiciones y expresiones orales, en la comunidad de Palopo Contadero, parroquia Ignacio Flores, cantón Latacunga. - De la Cruz Pumashunta, Marcela Karina (2018)
The research called "Study of the Immaterial Heritage of the Field 1: Traditions and Oral Expressions, in the Community of Palopo Contadero, Parroquia Ignacio Flores, and Latacunga Canton ". It was developed based on three established objectives. The first one was a Diagnosis in which the information was gathered in the geographical environmental, socio-economic and historical-cultural aspect through interviews with the residents of the Palopo Contadero community, to know the current status of the sector, in the second objective, the inventory of oral traditions and expressions was carried out using the INPC (National Institute of Cultural Heritage) files. At the present investigation, five sub-scopes of the oral traditions and expressions were obtained as a result: such as; legends, myths, loas, riddles and proverbs. With a total of 65 oral expressions of which: 34% are sayings, 23% are riddles, 20% could be found myths / beliefs, 12% of legends that only narrate the elderly, and 11% corresponds to the Loas, this has the lowest percentage because they are heard only at parties. The information was collected through interviews with the key actors of the Community, which allowed to obtain information to register the data in the inventory, in the third objective, the Guide of oral traditions and expressions was elaborated by systematizing the data obtained, which referred to the legends, myths / beliefs, loas, riddles and refrenes since the research proposed to safeguard and disseminate knowledge to future generations. It was possible to witness in this research that the current youth of 18-25 years do not possess any knowledge of legends, while older adults have a number of knowledge and knowledge that is still maintained. The lack of transmission of knowledge by parents is notorious in today's youth; young people are unaware of the myths, legends, stories, even the customs and traditions of their sector.